ECONOMIC EFFICIENCY OF WHEAT AND FABA BEAN PRODUCTION FOR SMALL SCALE FARMERS IN NORTHERN STATE - SUDAN - A. A. Ali; Imad E. E. Abdel Karim Yousif (Journal of Animal and Plant Sciences, 2012)
The objective of this paper was to estimate the economic efficiency of wheat and faba bean production for small-scale farmers in Northern State-Sudan using the stochastic frontier production and cost functions. A sample of 120 farmers from Dongola locality in the north and Ed-abba locality in the south of the state in 2004/05 winter season was selected using a randomized multi-stage stratified sampling technique. Stochastic frontier production and cost functions were used to estimate the economic efficiency of farmers. The results showed that the mean technical efficiencies of wheat were 0.75 and 0.66 in Dongola and Ed-abba, respectively, while for faba bean they were 0.65 and 0.71, the overall mean allocative efficiencies of wheat in the two localities were 0.72 and 0.68, whereas, they were 0.86, 0.84 for faba bean. The predicated overall mean of economic efficiencies that estimated as inverse of their cost efficiencies of wheat were 0.41 and 0.45 in the two localities, while in faba bean production they were 0.57 and 0.62 in Dongola and Ed-abba, respectively. That means farmers who cultivated faba bean were more economically efficient than farmers who cultivated wheat in the two localities and their allocative efficiencies were sources of gain.
Keywords: Economic Efficiency; Small Scale Farmers; Northern State; Sudan.